THE INFLUENCE OF TOP MANAGEMENT COMMITMENT ON FIRM PRODUCTIVITY THROUGH TOTAL QUALITY MANAGEMENT AND MANAGEMENT ACCOUNTING INFORMATION SYSTEM - Soemantri, Roebiandini (JURNAL ILMU MANAJEMEN DAN BISNIS, 2012)
This study examines the influence of top management commitment on firm productivity through implementation of total quality management and management accounting information systems. The research employed explanatory survey method. Data for this studywere drawn from a survey 73 Indonesia Manufacturing Firms having sertification of ISO 9000 series from 2004 up to 2006. The respondents of this research are production manager of each firm. Data were collected by indirect communication based on a questionnaireand study of documentation. Descriptive statistics were used to data analysis based on weighted mean score and path analysis. This studyused primary data and secondary data. The results are as follows : (1) there is a positive and significant influence of top management commitment toward implementation of total quality management; (2)there is a positive and significant influence of top managementcommitment on management accounting information systems; (3) there is a positive and significant influence of implementation of total quality management and management accounting information systems to firm productivity; (4) there is a positive and significant influence of top management commitment to firm productivity through implementation of total quality management; (5) there is a positive and significant influence of top management commitment to productivity through management accounting information systems; (6) there is a positive and significant influence of top management commitment on firm productivity through implementation of total quality management and management accounting information systems.